Preservice Chemistry Teacher Perception toward Contextual Learning Implementation of OLEDs in Organic Chemistry Learning - Septian Jauhariansyah; Oczhinvia Dwitasari; Ahmad Mudzakir; Tuszie Widhiyanti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aimed to explore chemistry pre-service teacher view toward implementation of contextual learning in Organic Chemistry. The context that was investigated about is Organic Light Emitting Diodes (OLEDs), which was a novel display technology that is being used for smartphone display. Seventeen pre-service chemistry teachers were interviewed about their knowledge about organic chemistry, conjugated double bond, OLEDs and their view about implementing OLEDs context in organic chemistry learning. Three groups of questions were asked to the pre-service chemistry teacher, most of them indicating lack knowledge about detail information of OLEDs even though they really appreciate if OLEDs was introduced in Organic Chemistry learning especially in conjugated double bond and nature-generated organic compound topics.